Prevalence of panic and agoraphobia in post COVID-19 patients - Visalakshi H. Subramanian; Viteja M.; Vijay K. Kumar (International Journal of Research in Medical Sciences, 2023)
Background: COVID-19 pandemic and quarantine of people who were tested positive made more cautious and anxious when being out in public. This study concentrates on the prevalence of panic and agoraphobia using panic and agoraphobia scale. Methods: Survey research study of 121 subjects using web-based data collection (Google form). Results: The result were obtained using panic and agoraphobia scale. Statistical analysis did not show considerable panic attack and agoraphobia in people who were tested positive for COVID-19. Conclusions: The study population did not show considerable panic attack and agoraphobia after being quarantined or hospitalised during 1st, 2nd and 3rd wave of COVID-19.